Maqāṣid al-Syarī‘ah sebagai Landasan Pengaturan Relasi Produsen–Konsumen dalam Hukum Ekonomi Islam di Indonesia - Sultan, Zulfadli; Muin, Rahmawati; Kara, Muslimin (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2026)
The interaction between producers and consumers in Islamic economics is not solely oriented towards economic efficiency and profit, but also towards ethical values and social welfare. This study aims to analyze the role of maqasid al-syariah as a normative basis in regulating the relationship between producers and consumers in Islamic economic law. This study is a qualitative literature review of classical and contemporary literature relevant to Islamic economics and maqasid al-syariah. The results show that maqasid al-syariah positions producers and consumers not only as economic actors but also as moral subjects who have a responsibility to protect religion, life, reason, offspring, and property. These principles guide production and consumption practices to be halal, fair, proportional, and free from exploitation. The implementation of maqasid al-syariah in producer-consumer relations contributes to strengthening market confidence, preventing inequality, and creating a fair and sustainable Islamic economic system.